Prediction of Erosion and Sedimentation in Micro Catchment Area of Air Lanang Using Soil and Water Assessment Tool (SWAT) Model - Teja Alta Putra; Kanang Setyo Hindarto; Priyono Prawito (TERRA : Journal of Land Restoration, 2022)
This research aims to obtain erosion and sedimentation rate data in the micro catchment area of Air Lanang using soil and water assessment tool (SWAT) modelling within existing and scenario land uses. Geographically, the study area is located between latitude 3°26`23.48” - 3°31`46.09” S and longitude 102°24`11.74” - 102°28`26.35” E with a total area of 2987.06 ha. Soil analysis was conducted in the Soil Science Laboratory, Faculty of Agriculture, University of Bengkulu. The research data was analysed using SWAT model. Recorded data in this study were including soil analysis data, soil type map from land unit and soil map book Bengkulu sheet (0912) Sumatra, data of status area from KLHK, Digital Elevation Model National data from BIG, a set of climate data from BMKG, data of administrative border from RBI map Bengkulu Province and data of land use from the interpretation of satellite image and ground checking, as well as the scenario land use which was prepared following the community forest program from the government in the protected forest by converting the coffee plantation located within the protected forest area to woody plants with economic, social and conservative values. The results showed total erosion in the micro catchment area of Air Lanang with the existing land use in 2020 was 820731.87 ton year-1, while in the scenario land use was 288212.45 ton/year which were classified to very light, light, moderate, heavy and very heavy in class erosion. Based on the existing land use data, there was a decrease of erosion in the moderate to very heavy class of erosion for 7.27 % resulting in the very light and light class of erosion become 15.55 % after the simulation of the scenario land use model. The use of scenario land use model is effective to decrease erosion and sedimentation rate. The total sedimentation in the micro catchment area of Air Lanang in existing land use in 2020 was 354949.98 ton year-1 with the highest sedimentation in sub-basin 2 while the lowest sedimentation was found in sub-basin 12. On the other hand, the total sedimentation in the scenario land use model was 137365.04 ton year-1. The reduction of total sedimentation in existing land use in 2020 to the scenario land use model was 36.76 %.